Combined electric and acoustic hearing performance with Zebra® speech processor: Speech reception, place, and temporal coding evaluation. (June 2013) - Vaerenberg, Bart; Péan, Vincent; Lesbros, Guillaume; De Ceulaer, Geert; Schauwers, Karen; Daemers, Kristin; Gnansia, Dan; Govaerts, Paul J
Abstract : Objective: To assess the auditory performance of Digisonic ® cochlear implant users with electric stimulation (ES) and electro-acoustic stimulation (EAS) with special attention to the processing of low-frequency temporal fine structure. Method: Six patients implanted with a Digisonic ® SP implant and showing low-frequency residual hearing were fitted with the Zebra ® speech processor providing both electric and acoustic stimulation. Assessment consisted of monosyllabic speech identification tests in quiet and in noise at different presentation levels, and a pitch discrimination task using harmonic and disharmonic intonating complex sounds (Vaerenberg et al ., 2011 ). These tests investigate place and time coding through pitch discrimination. All tasks were performed with ES only and with EAS. Results: Speech results in noise showed significant improvement with EAS when compared to ES. Whereas EAS did not yield better results in the harmonic intonation test, the improvements in the disharmonic intonation test were remarkable, suggesting better coding of pitch cues requiring phase locking. Discussion: These results suggest that patients with residual hearing in the low-frequency range still have good phase-locking capacities, allowing them to process fine temporal information. ES relies mainly on place coding but provides poor low-frequency temporal coding, whereas EAS also provides temporal coding in the low-frequency range. Patients with residual phase-locking capacities can make use of these cues.